Pengaruh Employee Downsizing Terhadap Kinerja Keuangan Perusahaan - Ghinaa Khoirunnisa; Jouzar Farouq Ishak (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Employee downsizing is one of the strategies that many carried out during the Covid-19 pandemic to reduce the company's costs while increasing revenue. Therefore, the authors conducted this study intending to find out the effect of employee downsizing on financial performance projected by Return on Asset (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The sampling technique used is purposive sampling by setting certain criteria so that obtained as many as 33 companies meet the criteria. The research method used is quantitative descriptive method with Multivariate Analysis of Variance (MANOVA) using SPSS 25. The result of this study is the known effect of employee downsizing on financial performance projected with ROA, ROE, and NPM is positive and significant simultaneously. Partially, employee downsizing has a positive and no significant effect on ROA or ROE but has a positive and significant effect on NPM.